2021
DOI: 10.3390/children8020114
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Factors between Childhood Traumatic Experiences and Eating Disorders Development: A Systematic Review

Abstract: Background: Many people with eating disorders often report having suffered some kind of childhood trauma. For this reason, many studies have attempted to explore the mediating factors between traumatic experiences and the development of eating disorders. The aim of our study is to conduct a systematic review of published works on the mediating factors between childhood trauma and the development of eating disorders. Method: This review was carried out up to 5 December, 2020, using the databases PsycInfo and Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
4
21
0
1
Order By: Relevance
“…Ayrıca literatürde travmatik yaşantılarla yeme bozukluklarının birlikte artıp azalma biçimindeki ilişkisi de vurgulanmaktadır (örn. Rabito-Alcón, Baile, & Vanderlinden, 2021;Rabito-Alcón, Baile, Vanderlinden, 2020;Palmisano et al, 2018;Scheffers et al, 2017). Çocukluk çağı ihmali ile bozulmuş yeme davranışı arasındaki ilişkiye dikkat çekilmektedir (Minnich., Gordon, Kwan, Troop-Gordon, 2017).…”
Section: Dolayısıylaunclassified
“…Ayrıca literatürde travmatik yaşantılarla yeme bozukluklarının birlikte artıp azalma biçimindeki ilişkisi de vurgulanmaktadır (örn. Rabito-Alcón, Baile, & Vanderlinden, 2021;Rabito-Alcón, Baile, Vanderlinden, 2020;Palmisano et al, 2018;Scheffers et al, 2017). Çocukluk çağı ihmali ile bozulmuş yeme davranışı arasındaki ilişkiye dikkat çekilmektedir (Minnich., Gordon, Kwan, Troop-Gordon, 2017).…”
Section: Dolayısıylaunclassified
“…The interaction between neurobiological substrates and environmental events is clearer when examining traumatic events (which are recorded more frequently in individuals with an ED), and this interaction might reveal the roles of environmental and genetic factors [ 6 , 7 , 8 ]. A growing body of literature has studied the role of traumatic events in developing EDs, even when the actual effects are still not well understood [ 9 , 10 ]. However, different studies have documented the presence of different biological scars in subjects with EDs and personal histories of maltreatment, in line with the hypothesis of a traumatic echo-phenotype of EDs [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the research is still inconclusive; some studies have found associations whereas some have not, and some researchers suggest associations are overstated (Polivy & Herman, 2002 ; Smyth et al, 2008 ; Villarroel et al, 2012 ). To better understand the possible relationship between childhood adverse experiences and AN, some authors have considered possible mediators such as dissociation (Pugh et al, 2018 ), anxiety and depression (Rabito‐Alcón et al, 2021 ) insecure attachment (Illing et al, 2010 ), and emotional dysregulation (Mills et al, 2015 ). For example, Rabito‐Alcón et al, 2021 suggested that eating disorders may have a variety of functions; eating disorders may function to suppress overwhelming emotions resulting from prior trauma, or may serve as a way of regulating other emotional experiences stemming from trauma, such as anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%